Duplication within chromosome 17p11.2 in 12 families of French ancestry with Charcot-Marie-Tooth disease type 1a. The French CMT Research Group. Issue 11 (November 1992) - Brice, A; Ravisé, N; Stevanin, G; Gugenheim, M; Bouche, P; Penet, C; Agid, Y
Abstract : Hereditary motor and sensory neuropathy type I (HMSN I), also designated Charcot-Marie-Tooth disease type 1 (CMT1), is a peripheral neuropathy frequently inherited as an autosomal dominant trait, characterised by progressive distal muscular atrophy and sensory loss with markedly decreased nerve conduction velocity. A duplication within chromosome 17p11.2, cosegregating with the disease, has recently been reported in several CMT1a families. In order to estimate the frequency of this anomaly and determine the location of a duplication in this region, 12 CMT1 families were analysed with polymorphic DNA markers located within 17p11.2-12. Duplications were found in all families including loci D17S61 (EW401), D17S122 (VAW409R3a and RM11-GT), and D17S125 (VAW412R3). The duplications were completely linked and associated with the disease (lod score of 20.77 at zero recombination). Screening for the RM11-GT microsatellite showed that most of the duplicated haplotypes were heterozygous, supporting the hypothesis that the duplication resulted from an unequal crossing over. There was no significant haplotype association within the duplicated region suggesting that the duplication resulted de novo as an independent event in each family. In one family, recombination within the duplicated region was observed, indicating that genetic instability in 17p11.2 might be related to a high recombination rate. Since most cases of CMT1a seem to result from this segmental trisomy, it can be used as a basis for DNA diagnosis of the disease.